Digestive suture failure - Puig, Roberto; Artucio, Hernán; D'Auria, Agustín; Crestanello, Francisco; Estefan, Alberto; Harretche, Martín; Martinez, José L.; Sarroca, Carlos (Cirugía del Uruguay, 1979)
No surgeon can deny having experienced leakage of digestive sutures. It is this complication that points to him as the one directly responsible fer omissions in pre-operative workout of his patient; far defect and/or errors in technique; for recognition of the situation as one of "leakage risk"; for the need of intensive care which will permit the early detection of this condition; and for the important responsability in indicating and carrying out reoperation.